ChemInform Abstract: Nanoporous BiVO4 Photoanodes with Dual‐Layer Oxygen Evolution Catalysts for Solar Water Splitting. Issue 21 (27th May 2014) - Kim, T. W.; Choi, K.‐S.
Abstract A high‐surface‐area, nanoporous BiVO4 electrode composed of particles smaller than its hole diffusion length can effectively increase the electron‐hole separation yield without additional doping.